The Existence of Artificial Intelligence in the Future - Ibrahim, Nur Aifiah Binti (Universitas Dinamika, 2023)
Artificial intelligence is arranged and communicates in a language structure to have a machine learning algorithm that picks up the faster solution in solving humanity’s problems. However, the separation between good and bad all comes down to the human’s intention and determination. Hence, it is crucial to look at the data patterns and come out with the most appropriate machine algorithm. The layering of nodes and information is forming to create a piece of new knowledge. It is a universal language algorithm that speaks with one another to convey the same message. In other words, dimensionality and data simplicity lure in more knowledge and understanding of the problem.